The role of personalisation in digital advertising on consumer decision making in the South African context. - Jansen, Bareile (University of the Witwatersrand, Johannesburg, 2024)
The surge in digital advertising has redefined the consumer landscape, profoundly impacting decision-making processes related to brand and product choices, which has ultimately led to digital brand saturation (Agrawani, 2022). Digital brand saturation could potentially lead to consumer decision making frustration, unnecessary marketing to the wrong audience, costly expenses related to that, and an increase in the need for personalisation (Agrawani, 2022). Despite extensive research on digital advertising's impact on consumer decisions, there is a lack of studies focusing on the effects of personalisation on consumer behaviour in South Africa. This study employs a qualitative approach, using semi-structured interviews analysed via thematic analysis, with convenience sampling to select the 20 participants for this study (Creswell & Creswell, 2018). This method was practical for gathering data efficiently within the study’s constraints. The findings of the study highlight the critical role of relevant advertising in engaging consumers and underscore the importance of ethical data practices to build consumer trust Drawing upon foundational literature in consumer behaviour, marketing ethics, and cross-cultural studies, this study seeked to inform decision-making and promote ethical practices in personalised advertising. The conclusions emphasise the critical importance of relevance, transparency, and consumer autonomy in developing effective advertising strategies and building trust in brand-consumer relationships. By integrating these elements, the study underscores the need for aligning advertising practices with ethical standards to foster meaningful and trustworthy interactions between brands and consumers.
A research dissertation submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital Advertising; Personalisation; Artificial Intelligence; Targeting; Consumer Behaviour; Data Mining; UCTD; SDG-8: Decent work and economic growth